College students’ preferences for written corrective feedback - Lucia Geneviave Bella Shinta; Utari Praba Astuti; Nova Ariani (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
Although written corrective feedback (WCF) is provided to give students information about their writing which intends to help them make improvement, students may have different expectations of how WCF should be delivered. This study was focused on investigating English Language Education (ELE) students’ preferences for the WCF covering the preferences for amount of feedback, writing aspects to focus on, correction techniques, and tones of feedback. A number of 188 ELE students participated in this study. Using mixed-methods design to collect data, the study revealed that the students expected to always have WCF on their errors as they have desire to always make improvement. Having WCF is considered essential as some students had difficulty analyzing errors independently. Besides believing the importance of all aspects of writing, the students mentioned some reasons related to their weaknesses that require focuses on all feedback. Most of the students preferred direct feedback and indirect feedback with location and indication of error types as they valued detailed feedback. The students saw feedback in negative tone and suggestive tone as the source of improvement, while one in positive tone increased positive feelings towards writing. The findings suggest the importance of increasing the students’ awareness of how to get benefits from different WCF techniques while still accommodating their preferences.